(untitled) (ouvirOUver, 2017)
RESUMO Esse trabalho aborda questões relacionadas à escolha e utilização do espaço para apresentações de Teatro de Rua, buscando perceber a influência que este pode determinar sobre a encenação nele apresentada. Além da relação direta entre esses dois elementos, estabelecem-se também a percepção e inferência que o espectador faz Ã obra artística a partir de suas referências acerca do local onde ocorre a encenação. Assim, a análise decorre da tríade espaço/espetáculo/espectador. O estudo realizado nesse artigo é um recorte oriundo da pesquisa de mestrado iniciada em 2013 no Programa de Pós-graduação em Artes da Universidade Federal de Uberlândia - UFU. ABSTRACT This paper addresses issues related to the choice and use of space for Street Theater performances, seeking to realize the influence that each place can determine on the scenario presented in it. In addition to the direct relationship between the elements - space and spectacle - the perception and inference that the spectator makes the artistic work from their references about where the scenario occurs . Thus, the analysis results from the triad space/spectacle/spectator. The study in this article is an excerpt coming from the master’s research started in 2013 at the Graduate Program in Arts of the Federal University of Uberlândia - UFU. KEY-WORDS Street Theater, space, spectacle, spectator.